Glycemic Control and Survival in Peritoneal Dialysis Patients with Diabetes Mellitus - Duong, Uyen (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: The optimal target for glycemic control has not been established for diabetic peritoneal dialysis (PD) patients. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We examined mortality-predictability of hemoglobin A1c random serum glucose in a contemporary cohort of diabetic PD patients treated in DaVita dialysis clinics July 2001 through June 2006 with follow-up through June 2007. RESULTS: We identified 2798 diabetic PD patients with A1c data. Serum glucose correlated with A1C (r = 0.51). Adjusted all-cause death hazard ratio and 95% confidence interval for baseline A1c increments of 7.0 to 7.9%, 8.0 to 8.9%, 9.0 to 9.9%, and ≥10%, compared with 6.0 to 6.9% (reference), were 1.13 (0.97 to 1.32), 1.05 (0.88 to 1.27), 1.06 (0.84 to 1.34), and 1.48 (1.18 to 1.86); and for time-averaged A1c values were 1.10 (0.96 to 1.27), 1.28 (1.07 to 1.53), 1.34 (1.05 to 1.70), and 1.81 (1.33 to 2.46), respectively. The A1c-mortality association was modified by hemoglobin level such that higher all-cause mortality was evident only in nonanemic patients. Similar but non-significant trends in cardiovascular death risk was found across A1c increments. Adjusted all-cause death HR for time-averaged blood glucose 150 to 199, 200 to 249, 250 to 299, and ≥300 mg/dl, compared with 60 to 99 mg/dl (reference), were 1.02 (0.70 to 1.47), 1.12 (0.77 to 1.63), 1.45 (0.97 to 2.18), and 2.10 (1.37 to 3.20), respectively. CONCLUSIONS: Poor glycemic control appears associated incrementally with higher mortality in PD patients. Moderate to severe hyperglycemia is associated with higher death risk especially in certain subgroups.